The Evolution of T Cell Depleted Haploidentical Transplantation - Aversa, Franco; Pierini, Antonio; Ruggeri, Loredana; Martelli, Massimo Fabrizio; Velardi, Andrea (Frontiers in Immunology, 2019)
Work on hematopoietic stem cell transplantation from one haplotype mismatched (haploidentical) donor has been proceeding for over 20 years all over the world and new transplant procedures have been developed. Some centers have focused on the conditioning regimens and post-transplant immune suppression; others have concentrated on manipulating the graft. The graft may be a “megadose” of extensively T-cell depleted peripheral blood progenitor cells or unmanipulated bone marrow or peripheral blood cells. Haploidentical transplant modalities are based on high intensity conditioning regimen but reduced intensity regimens have recently been introduced. Excellent engraftment rates are associated with a very low incidence of graft-versus-host disease and regimen related mortality even in patients who are over 50 years old. Overall, event-free survivals compare favorably with reports on transplants from sources of stem cells other than the matched sibling. Improvements will come with successful implementation of strategies to accelerate and strengthen post transplant immune reconstitution and to prevent leukemia relapse.